2022
DOI: 10.1186/s12879-022-07446-8
|View full text |Cite
|
Sign up to set email alerts
|

Protease and gag diversity and drug resistance mutations among treatment-naive Mexican people living with HIV

Abstract: Introduction In Mexico, HIV genotyping is performed in people living with HIV (PLWH) failing their first-line antiretroviral (ARV) regimen; it is not routinely done for all treatment-naive PLWH before ARV initiation. The first nationally representative survey published in 2016 reported that the prevalence of pretreatment drug mutations in treatment-naive Mexican PLWH was 15.5% to any antiretroviral drug and 10.6% to non-nucleoside reverse transcriptase inhibitors (NNRTIs) using conventional San… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…In addition to the mutations associated with resistance to PIs, more than half of the samples presented deletions and insertions in the protein-coding region of the matrix (p17), presenting greater sequence variation compared to the capsid. This pattern is consistent with similar studies that have also reported more quasispecies diversity, polymorphisms, deletions, and insertions in the matrix p17 21 , 22 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition to the mutations associated with resistance to PIs, more than half of the samples presented deletions and insertions in the protein-coding region of the matrix (p17), presenting greater sequence variation compared to the capsid. This pattern is consistent with similar studies that have also reported more quasispecies diversity, polymorphisms, deletions, and insertions in the matrix p17 21 , 22 .…”
Section: Discussionsupporting
confidence: 92%
“…Mutations at cleavage sites can directly affect the interaction with PI, whereas mutations at non-cleaved sites can contribute to restoring viral fitness, thus improving the access of the viral protease to the cleavage site 11 , 20 . Comparatively, a study conducted in Mexico showed a higher prevalence of the R76K and H219Q mutations and lower prevalence of the V128I and Y132F mutations among treatment-naïve individuals 21 .…”
Section: Discussionmentioning
confidence: 89%
“…Additional articles were identified by experts in the field. We screened out 1330 studies after removing duplicates, and 140 articles were downloaded for full-length screening, of which 39 articles were kept [ 6 , 17 , 24 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Not surprisingly, we observed very few mutations to PIs, an expected result due to the high genetic barrier of this class of drugs. However, we identified the M46I as the most common mutation to PIs, also reported at a low frequency in ART-naïve individuals in Mexico, which is associated with reduced susceptibility to ATV and LPV [ 16 ]. The N88S mutation, conferring high-level resistance to ATV, was detected in one subject.…”
Section: Discussionmentioning
confidence: 99%